2001
DOI: 10.1590/s0037-86822001000300004
|View full text |Cite
|
Sign up to set email alerts
|

A urbanização das leishmanioses e a baixa resolutividade diagnóstica em municípios da Região Metropolitana de Belo Horizonte

Abstract: 30, 53, 64, 53 and 84, respectively. In 19 (61.3%) municipalities no reference center for the diagnosis of the infection was available, so that most of the patients (80%) were referred to Belo Horizonte. Twelve (39%) municipalities have a center for leishmaniasis evaluation, however in only eight (67%) of these basic specific diagnostic tests were available. Rapid and extensive increase of leishmaniasis associated with low diagnosis capacity has been observed in the metropolitan area of Belo Horizonte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 9 publications
0
27
0
6
Order By: Relevance
“…Nestes, o cão é considerado o principal reservatório doméstico, e estudos demonstram que altas taxas de prevalência canina estão associadas à ocorrência de casos humanos (Bevilacqua et al, 2001;Luz et al, 2001).…”
unclassified
“…Nestes, o cão é considerado o principal reservatório doméstico, e estudos demonstram que altas taxas de prevalência canina estão associadas à ocorrência de casos humanos (Bevilacqua et al, 2001;Luz et al, 2001).…”
unclassified
“…Machado de Assis et al 15 conducted a prospective study to validate diagnostic tests for VL in Brazil and found that the average period between symptom onset and confirmation of diagnosis was 53 days (ranging of 5 to 360 days). This finding indicates the need for awareness and training of health care professionals, as highlighted by Luz et al 16 , and the need to provide simple, accurate, and fast diagnostic tests. These actions, which have a direct impact on the period between patient diagnosis and treatment, can reduce the high rates of morbidity and mortality due to VL in Brazil.…”
Section: Discussionmentioning
confidence: 83%
“…No Brasil, o principal vetor da leishmaniose são insetos flebotomíneos do gênero Lutzomyia (popularmente conhecido como "mosquito palha", "cangalhinha", entre outros), tendo os cães como seu principal reservatório doméstico, propiciando um crescente número de casos de leishmaniose nos grandes centros urbanos 20 . De acordo com a Organização Mundial da Saúde (OMS) 19 , no Brasil, as leishmanioses constituem grave problema de saúde pública, sendo a leishmaniose tegumentar americana diagnosticada em praticamente todos os Estados brasileiros e a leishmaniose visceral, notificada em 17 Estados, atingindo quatro das cinco regiões geográficas do país.…”
Section: As Leishmanioses Na Históriaunclassified